1990
DOI: 10.1016/0014-5793(90)81414-j
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes of aminoacyl‐tRNA and unchanged tRNA upon complex formation with polypeptide chain elongation factor Tu

Abstract: The conformation change of Thermus thermophilus tRNA~ le upon complex formation with T. thermophilus elongation factor Tu (EF-Tu) was studied by analysis of the circular dichroism (CD) bands at 315 nm (due to the 2-thioribothymidine residue in the T-loop) and at 295 nm (due to the core structure of tRNA). Formation of -Ile the ternary complex of lsoleucyl-tRNA 1 and EF-Tu.GTP increased the intensities of these CD bands, indicating stabilization of the association between the T-loop and the D-loop and also a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These are (i) the magnitudes of the macromolecular conformational changes that are elicited by ternary complex formation, (ii) the orientation of the anticodon stem with respect to the protein (e.g., in Figure 4 compare B with F and C with E), and (iii) the extension of the flexible 3' end of the aa-tRNA on the EF-Tu and the resultant extent of contact between the acceptor arm and the protein. Conformational changes occur in the aa-tRNA (Janiak et al, 1990, and references therein;Haruki et al, 1990) and in the EF-Tu (Kjeldgaard et al, 1993, and references therein;Jonák et al, 1994) upon ternary complex formation, but the magnitudes of these changes have not been quantified. Since iodide ion quenching data have shown that the solvent accessibility of the fluorescein attached to s4U is unaltered when the ternary complex is formed (Adkins et al, 1983) and dynamic polarization data have shown that the local motion of the dye was unaffected by ternary complex formation (Hazlett et al, 1989), it is clear that EF-Tu does not cover or contact the surface of the aa-tRNA near s4U in the ternary complex.…”
Section: Discussionmentioning
confidence: 99%
“…These are (i) the magnitudes of the macromolecular conformational changes that are elicited by ternary complex formation, (ii) the orientation of the anticodon stem with respect to the protein (e.g., in Figure 4 compare B with F and C with E), and (iii) the extension of the flexible 3' end of the aa-tRNA on the EF-Tu and the resultant extent of contact between the acceptor arm and the protein. Conformational changes occur in the aa-tRNA (Janiak et al, 1990, and references therein;Haruki et al, 1990) and in the EF-Tu (Kjeldgaard et al, 1993, and references therein;Jonák et al, 1994) upon ternary complex formation, but the magnitudes of these changes have not been quantified. Since iodide ion quenching data have shown that the solvent accessibility of the fluorescein attached to s4U is unaltered when the ternary complex is formed (Adkins et al, 1983) and dynamic polarization data have shown that the local motion of the dye was unaffected by ternary complex formation (Hazlett et al, 1989), it is clear that EF-Tu does not cover or contact the surface of the aa-tRNA near s4U in the ternary complex.…”
Section: Discussionmentioning
confidence: 99%
“…The conformation of aminoacyl-tRNA in the complex with EF-Tu-GTP was reported to differ from that in solution. The changes have been suggested by results obtained with various approaches, including electron spin resonance (Weygand-Durasevic et al, 1981), circular dichroism (Haruki et al, 1990), oligonucleotide binding (Kruse et al, 1980), nuclease digestion (Boutorin etal., 1981;Wikman etal., 1982), chemical modification (Riehl et al, 1983), and fluorescence (Adkins et al, 1983; Janiak et al, 1990). The affected regions of the tRNA molecule include the 3' terminus and the T stem, i.e., two regions which directly interact with the factor (Wikman et al, 1987;Joshi et al, 1986;Boutorin et al, 1981;Picone & Parmeggiani, 1983), as well as the anticodon loop, thiouridine(S), and the D loop, i.e., regions which are not in contact with the protein (Wikman et al, 1982;W.…”
mentioning
confidence: 99%
“…A hypothesis exists that the specificity encountered in the tRNAaminoacyl:tRNA synthetase interactions are due to certain aspects of conformation of tRNA [4]. From recent data, it is known that the conformation of free and aminoacylated tRNA are different as was deduced by CD measurements [5]. At high pressure the structure of transfer ribonucleic acids (tRNA) and ribosomal SS RNA undergo some conformational changes .…”
Section: Nonenzymatic Trna Aminoacylationmentioning
confidence: 99%